Sensing surface mechanical deformation using active probes driven by motor proteins - Daisuke Inoue (Nature Portfolio, 2016)
It is challenging to characterize the mechanical properties of soft surfaces owing to the coupling between surface deformation and elasticity of bulk materials. Here, Inoue et al. use motile cytoskeletal filaments as active probes, whose direction reflects the stress field experienced by the surface.